THE DOCK ESTABLISHMENT TO SUPPORT MARITIME SECURITY OPERATIONS IN BANGKA BELITUNG - Sunardi, Asep Didi; Faisol, Achmad; Samudro, Eko G. (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
Navy Base of Bangka Belitung is a type B Navy Base under the operation of Main Navy Base III Jakarta. As a base, it has an important role in the series of Integrated Fleet Weapon Systems (Sistem Senjata Armada Terpadu, SSAT). Nave Base of Bangka Belitung has the main task of supporting administration and logistics for operation elements. Besides that, it plays the role of a unit that enforces the law and maintains maritime security, and also plays an active role in empowering the marine defense area. The port is an important facility in supporting the presence of navy elements that can provide a deterrence effect against threats to maritime security. However, the absence of a dock at Bangka Belitung Navy Base will limit the power of the navy element, that is why the process of law enforcement at sea will be carried out optimally with the presence of a dock. The purpose of this study was to analyze the dock establishment to support the navy power in Bangka Belitung Navy Base securing its maritime area. The theories used were sea power theory, maritime security, dock concept, and International Ship and Port Security Code (ISPS Code). This study used the literature review method, primary data obtained through important files related to the object of research and supported by secondary data in the form of books, journals, and documents related to the construction of the Navy Base of Bangka Belitung. The results showed that the dock can improve the performance of Bangka Belitung Navy Base elements in the support function of anchorage facilities, support for ship maintenance and repair facilities as well as support for supply facilities, support for law enforcement, and maintaining maritime security, as well as empowering marine areas